2013
DOI: 10.1093/cid/cit437
|View full text |Cite
|
Sign up to set email alerts
|

HIV Incidence Among Men With and Those Without Sexually Transmitted Rectal Infections: Estimates From Matching Against an HIV Case Registry

Abstract: One in 15 MSM with rectal infections was diagnosed with HIV within a year, a higher risk than for MSM without rectal infections. Such data have implications for screening for rectal STD, and may be useful for targeting populations for risk-reduction counseling and other HIV prevention strategies, such as preexposure prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(102 citation statements)
references
References 22 publications
4
83
0
8
Order By: Relevance
“…After extensive control for confounding by behavioral risk with propensity score-weighted models, MSM diagnosed with rectal STI during study follow-up were more than 2.5 times as likely to acquire HIV as MSM not diagnosed with Previous studies have highlighted the importance of rectal STI in HIV acquisition in U.S. MSM, but these studies were conducted in STI clinic settings, which could bias toward a higher behavioral risk population with more symptomatic STIs. 26,27 In addition, these studies relied on passive case finding and did not observe incident STIs and HIV diagnoses prospectively as did our study. One longitudinal cohort study conducted in Australia also showed an association between a combined exposure of self-reported and study-diagnosed rectal STI and HIV; however, it is not clear if these results apply to a sample of black and white MSM in the United States with substantially higher rates of both STI and HIV.…”
Section: Discussionmentioning
confidence: 99%
“…After extensive control for confounding by behavioral risk with propensity score-weighted models, MSM diagnosed with rectal STI during study follow-up were more than 2.5 times as likely to acquire HIV as MSM not diagnosed with Previous studies have highlighted the importance of rectal STI in HIV acquisition in U.S. MSM, but these studies were conducted in STI clinic settings, which could bias toward a higher behavioral risk population with more symptomatic STIs. 26,27 In addition, these studies relied on passive case finding and did not observe incident STIs and HIV diagnoses prospectively as did our study. One longitudinal cohort study conducted in Australia also showed an association between a combined exposure of self-reported and study-diagnosed rectal STI and HIV; however, it is not clear if these results apply to a sample of black and white MSM in the United States with substantially higher rates of both STI and HIV.…”
Section: Discussionmentioning
confidence: 99%
“…This may be as a surrogate marker of sexual risk, or due to changes in local inflammation and immunity, enhancing susceptibility (93)(94)(95)(96). Infection of the urethra (and possibly rectum) may increase likelihood of HIV transmission in HIV-positive MSM (97), although interim data from the PARTNER study showed no transmissions from men with undetectable HIV viral loads, despite significant rates of incident bacterial STI (98).…”
Section: Chlamydia and Gonorrhoeamentioning
confidence: 99%
“…The presence of an acute STI, such as syphilis, chlamydia and gonorrhoea, is associated with increased HIV acquisition (228), the strongest association being with rectal infections (94,95,229). HIV incidence varied by the rate of incident syphilis, when controlled for known predictors of HIV in the iPrEx study of HIV PrEP (230).…”
Section: Sti and Hiv Testing 231 Recall Arrangements And Frequency mentioning
confidence: 99%
“…[44][45][46] Irrespective of antiretroviral therapy, urethral chlamydia or gonorrhoea can increase seminal HIV viral load and thus infectiousness among HIV-positive MSM. 47 Therefore, regular STI testing among HIV-positive MSM is likely to have public as well as individual health benefits.…”
Section: -32mentioning
confidence: 99%